Fuzzimetric Type-2 Sets Representation Using Fuzzimetric Arcs - Kouatli, Issam (2014)
This paper proposes the implementation of Fuzzimetric Arcs concept, which was originally designed for Fuzzy Type-1. The concept has been extended in this paper to accommodate the Fuzzy type-2 notation. The new proposed representation of Fuzzy Type-2, termed in this paper as Fuzzimetric Type-2, includes the definition of “Degree of Fuzziness” (DOF), that allows the fuzzy set to be located fuzzily (randomly) between upper and lower bounds as defined in this paper. It has been shown that Fuzzimetric Type-1 is only a subset of Fuzzimetric Type-2 by setting the DOF value to zero.